PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT INFOMEDIA NUSANTARA LAYANAN TAM CONSUMER BSD - Marlina; Suryani, Lilis (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of work discipline and motivation on employee performance at PT Infomedia Nusantara Services BSD Consumer TAM, both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and the sample obtained in this study was 65 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that work discipline has a significant effect on employee performance with the regression equation Y = 14,672 + 0.618 (X1). The coefficient of determination value is 43.0%. Hypothesis testing obtained Tcount > Ttable or (6.897 > 1.998). Thus, Ho is rejected and H1 is accepted, meaning that there is a significant influence of work discipline on employee performance. Motivation has a significant effect on employee performance with the regression equation Y = 15.972 + 0.628 (X2). The coefficient of determination value is 41.1%. Hypothesis testing obtained Tcount > Ttable or (6.635 > 1.998). Thus, Ho is rejected and H₂ is accepted, meaning that there is a significant influence of motivation on employee performance. Work discipline and motivation have a significant effect on employee performance with the regression equation Y = 7.198 + 0.421 (X1) + 0.410 (X2). The coefficient of determination value was 56.2%, while the remaining 43.8% was influenced by other variables not used in this research. Hypothesis testing obtained a value of Fcount > Ftable or (39,747 > 2,750). Thus, Ho is rejected and H3 is accepted, meaning that there is a significant simultaneous influence of work motivation and work environment on employee performance